Spontaneous abdominal wall endometriosis: A Case Report and review of the literature - Evelyn Yang; Gin-Den Chen; Yun-Han Liao (Elsevier, 2023)
Objective: We present a case of spontaneous abdominal wall endometriosis presenting as a painless nodular mass in a woman with no prior history of abdominal surgery. Case report: Abdominal wall endometriosis (AWE) is an uncommon form of endometriosis, usually arising due to a past history of cesarean section or abdominal hysterectomy. However, in rare cases, abdominal wall endometriosis can arise in women with no prior history of abdominal surgery. A 48-year-old woman presented to our obstetrics and gynecology clinic with a painless nodular mass in the right lower quadrant of the abdomen. Abdominal wall ultrasound showed a hypoechoic heterogenous mass under the skin. Wide surgical resection of the mass was conducted and post-operative histopathological report revealed abdominal wall endometriosis. Conclusion: Spontaneous abdominal wall endometriosis is an uncommon pathologic condition in which accurate diagnosis is difficult. As an increasing number of obstetrical and gynecological procedures are conducted worldwide, surgeons should keep this clinical entity in the differential diagnosis of any abdominal mass in reproductive-aged females regardless of their past surgical history.